Xylella fastidiosa em oliveiras (Olea europaea): distribuição na planta, transmissão vertical e diagnose - Santos, Beatriz de Nadai Gasparini (2022)
As consequence of the recent occurrence of the disease known as Olive Quick Decline Syndrome (OQDS), caused by Xylella fastidiosa subsp. pauca (Xf-p), in olive trees (Olea europaea) there is a lack of scientific information about the biology of this pathogen in olive trees that can help to understand this pathogen and support discussions about management strategies. From these numerous gaps in the practical knowledge of this pathogen, this work has as objectives: 1. to evaluate the occurrence of vertical transmission of the bacterium; 2. to determine the distribution of Xf-p in plants with different degrees of severity; and 3. to establish a low-cost diagnostic method with the possibility of execution "in farm". Olive branches taken from an asymptomatic plant, but infected with Xf-p, were propagated in a greenhouse and the resulting seedlings were analyzed for the presence of the pathogen by real-time quantitative PCR (q-PCR). The estimated vertical transmission rate at 32 months was 57.74% (41 of 71 nursery plants) and only one plant of the 28 Xf-p-infected (0.014%) showed symptoms of OQDS. To achieve the second objective, samples from 3 plants of the cultivar 'Grapollo' showing low OQDS severity (only one branch with symptoms) and one with symptoms generalized throughout the canopy (high severity) were collected at different positions in the canopy and root system and analyzed for the presence of Xf-p by qPCR. Even under conditions of low ORDS severity positive diagnoses for Xf-p were obtained between 30% and 57% of the samples collected on asymptomatic branches, while on symptomatic branches 77% of the samples were positive. On the other hand, in plants with high incidence of OQDS 82 to 100% of samples were positive. Finally, the diagnostic method based on printing of branch extracts on nitrocellulose membranes and identification of Xf-p by serology (Tissue-Print: TP - objective 3) showed promise, but with needs for improvement since the agreement of the results between TP and qPCR techniques was only slightly partial (K = 0.01 to 0.20) according to the Cohen-Kappa index.